THE EFFICACY OF EPLEY MANEUVER IN TREATING BENIGN PAROXYSMAL POSITIONAL VERTIGO - Kamil Rajczyk; Dominika Błonka; Janina Pohrybieniuk; Maria Irena Grys; Filip Kochański; Karolina Wołk; Aleksandra Jaskulska; Jan Pietrzak; Magdalena Bartold; Magda Skudzińska (International Journal of Innovative Technologies in Social Science, 2026)
Benign paroxysmal positional vertigo (BPPV) constitutes the most common cause of peripheral vertigo, significantly reducing patients’ quality of life. The Epley maneuver is considered the gold standard treatmen, though its effectiveness depends on many factors, and recurrences remain a significant clinical problem. Objective: Systematic evaluation of the effectiveness of the Epley maneuver in treating BPPV based on current literature, including factors influencing treatment efficacy and recurrence rates. Materials and methods: A systematic review was conducted according to PRISMA guidelines. We analyzed 32 studies (including 17 RCTs, 5 meta-analyses and 10 cohort studies) from 1990-2025, identified in PubMed, Cochrane Library and Embase databases. Inclusion criteria comprised: confirmed BPPV diagnosis, use of the Epley maneuver, and efficacy assessment. Case reports and studies without control groups were excluded. Results: The average effectiveness of the Epley maneuver is 85-90% after the first session for posterior canal BPPV [7,13]. Factors reducing effectiveness: age >65 years (70% vs 90%; p<0.05) [3], delayed treatment (>7 days: 75% vs 90%; p<0.01) [6,15], coexisting diabetes/migraine [15,16]. Recurrences occur in 30-50% of patients within one year [17,18]. Technique modifications (e.g., changed rotation angle) increase effectiveness to 95% (p=0.04) [14]. Conclusions: The Epley maneuver remains a highly effective method for treating BPPV, but requires individualization in elderly patients and those with comorbidities. Further research is needed on strategies to reduce recurrences and standardize protocols.